Does education lead to higher generalized trust? The importance of quality of government. (September 2016) - Charron, Nicholas; Rothstein, Bo
Highlights: The relationship between an individual's level of education and generalized trust is investigated. The positive effect of education on trust is contingent upon the quality of political institutions in one's country or region. The multi-level interaction is tested with new survey data for 24 European countries and over 85, 000 individuals. Strong support is found for a positive link between education and trust at the individual level when quality of institutions is high. The effect of one's education on trust is negligible when quality of institutions is low. Abstract: Generalized trust has become a prominent concept at the nexus of several disciplines, and the wide differences in trust between different societies continue to puzzle the social sciences. In this study, we explore the effects of micro and macro level factors in explaining an individual's propensity to 'trust others'. We hypothesize that higher levels of education will lead to higher social trust in individuals, given that the context (country or regions within countries) in which they reside has a sufficiently impartial and non-corrupt institutional setting. However, the positive effect of education on trust among individuals is expected to be negligible in contexts with greater levels of corruption and favoritism toward certain people are more inclined to view the system as 'rigged' as they become more educated. This multi-level interaction effect is tested using original survey data of 85, 000 individuals in 24 European countries. Using hierarchical modelling, we find strong support for our hypothesis. This effect is robust to a number of specifications, and even holds for regional variation of institutional quality (QoG) within countries – with the strongest effects being higher education – yet the country effects of QoG are strongest.